Developing a Course on Human-Centered Machine Learning-Based Product Design - Eui-Chul Jung; Meile Le (IAFOR Journal of Education, 2024)
Interpreting and incorporating machine learning technology from a human perspective helps define the role of product designers in the era of artificial intelligence. With this background, this study developed a 7-week design course about machine learning-based product design. Subsequently, in Fall 2023, a class with seven undergraduate students from different majors was held on the subject of “home camera.” The design process consisted of (a) user research and need definition based on machine learning understanding and (b) machine learning-based interaction design development using a coding platform. The course was designed to explore the role of designers who implement human-centered design planning and prototypes considering machine learning tools. In addition, the course provided a basis for suggesting the direction of design education methods given emerging AI technology. The essence of design education is not merely about efficiency; rather, it is about nurturing designers’ ability to think critically and use tools to cultivate innovation.